The Value of Diffusion Kurtosis Imaging in Detecting Delayed Brain Development of Premature Infants - Zhao, Xin; Zhang, Chunxiang; Zhang, Bohao; Yan, Jiayue; Wang, Kaiyu; Zhu, Zitao; Zhang, Xiaoan (Frontiers in Neurology, 2021)
Objective Preterm infants are at high risk of adverse neurodevelopmental outcome. Our aim is to explore the value of diffusion kurtosis imaging (DKI) in diagnosing brain developmental disorders in premature infants. Materials and Methods A total of 52 subjects were included in this study, including 26 premature infants as the preterm group, and 26 full-term infants as the control group. Routine MRI and DKI examination were performed. Mean kurtosis (MK), radial kurtosis (RK), fractional anisotropy (FA), mean diffusivity (MD) values were measured in the brain regions including posterior limbs of the internal capsule (PLIC); anterior limb of internal capsule (ALIC); parietal white matter (PWM); frontal white matter (FWM); thalamus (TH); caudate nucleus (CN); genu of the corpus callosum (GCC). The X2, t test, Spearman’s correlation analysis and receiver operating characteristic curve were used for data analyses. Results In the premature infant group, the MK and RK values of PLIA, ALIC, and PWM were lower than those in the control group (P<0.05). The FA values of PWM, FWM and TH were also lower than those of the control group (P<0.05). The area under curves of MK in PLIC and ALIC, MD in PWM, and FA in FWM were 0.813, 0.802, 0.842 and 0.867 (P<0.05). In thalamus and caudate nucleus, the correlations between MK, RK values and postmenstrual age (PMA) were higher than those between FA, MD values and PMA. Conclusions DKI can be used as an effective tool in detecting brain developmental disorders in premature infants.